CULTIVATION CONDITIONS FOR PROTEASE PRODUCTION BY A THERMO-HALOSTABLE BACTERIAL ISOLATE PLS A - Teuku M. Iqbalsyah; Malahayati Malahayati; Atikah Atikah; Febriani Febriani (Universitas Syiah Kuala, 2019)
Polyextremophiles have increasingly been utilised to produce thermostable enzymes with better stability in multiple extreme conditions. This study reports the screening results of four new bacterial isolates (PLS A, PLS 75, PLS 76 and PLS 80), isolated from an under water hot springs, in producing thermo-halostable protease enzyme. Optimum cultivation conditions for the protease production were also studied. Screening of protease-producing isolates was conducted using Thermus solid medium enriched with 3% skim milk and 0.5% casein. The growth of the isolates showing protease activity was monitored by measuring the cell dry weight and protease activity during 24 h cultivation period. The activity was also measured at various cultivation conditions, i.e. temperature, pH and salt concentrations. Amongst the four isolates, only PLS A showed the ability to produce protease. The optimum cultivation conditions for protease production were observed at 65°C, pH 7 for 18 h incubation. The activity increased with the addition of 1% NaCl concentration (0.085 Unit/mL). The ability of PLS A isolate to produce thermo-halostable protease was encouraging as they could potentially be used in industries requiring the enzyme with multiple extremes.